Prophylactic abdominal drainage following appendectomy for complicated appendicitis: A meta-analysis - Liao, Jiankun; Zhou, Jiansheng; Wang, Jialei; Xie, Guisheng; Wei, Haotang (Frontiers in Surgery, 2023)
Background To date, the value of prophylactic abdominal drainage (AD) following appendectomy in patients with complicated appendicitis (CA), including adults and children, has yet to be determined. This paper presents a meta-analysis of the effects of prophylactic AD on postoperative complications in patients with CA, with the goal of exploring the safety and effectiveness of prophylactic AD. Methods PubMed, Science Direct, Web of Science, Cochrane Library, and Embase databases were searched for relevant articles published before August 1, 2022. The primary outcomes were the complication rates [overall incidence of postoperative complications, incidence of intra-abdominal abscess (IAA), wound infection (WI), and postoperative ileus (PI), and the secondary outcome was the perioperative outcome]. The meta-analysis was performed with STATA V. 16.0A. Results A total of 2,627 articles were retrieved and 15 high-quality articles were eventually included after screening, resulting in a total of 5,123 patients, of whom 1,796 received AD and 3,327 did not. The results of this meta-analysis showed that compared with patients in the non-drainage group, patients in the drainage group had longer postoperative length of hospitalization (LOH) (SMD = 0.68, 95% CI: 0.01–1.35, P = 0.046), higher overall incidence of postoperative complications (OR = 0.50, 95% CI: 0.19–0.81, P = 0.01), higher incidence of WI (OR = 0.30, 95% CI: 0.08–0.51, P = 0.01) and PI (OR = 1.05, 95% CI: 0.57–1.54, P = 0.01), the differences were statistically significant. However, there was no significant difference in the incidence of IAA (OR = 0.10, 95% CI: −0.10 to 0.31, P = 0.31) between the two groups. The results of subgroup meta-analysis showed that in the adult subgroup, the overall incidence of postoperative complications in the drainage group was higher than that in the non-drainage group (OR = 0.67, 95% CI: 0.37–0.96, P = 0.01). However, there were no significant differences in IAA (OR = 0.18, 95% CI: −0.28 to 0.64, P = 0.45) and WI (OR = 0.13, 95% CI: (−0.40 to 0.66, P = 0.63) and PI (OR = 2.71, 95% CI: −0.29 to 5.71, P = 0.08). In the children subgroup, there were no significant differences in the incidence of IAA (OR = 0.51, 95% CI: −0.06 to 1.09, P = 0.08) between the two groups. The overall incidence of postoperative complications (OR = 0.46, 95% CI: 0.02–0.90, P = 0.04), incidences of WI (OR = 0.43, 95% CI: 0.14–0.71, P = 0.01) and PI (OR = 0.75, 95% CI: 0.10–1.39, P = 0.02) were significantly higher than those in the non-drainage group. Conclusion This meta-analysis concluded that prophylactic AD did not benefit from appendectomy, but increased the incidence of related complications, especially in children with CA. Thus, there is insufficient evidence to support the routine use of prophylactic AD following appendectomy.